2014
DOI: 10.1146/annurev-genet-120213-092007
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Neisseria Species

Abstract: Neisseria gonorrhoeae and Neisseria meningitidis are closely related organisms that cause the sexually transmitted infection gonorrhea and serious bacterial meningitis and septicemia, respectively. Both species possess multiple mechanisms to alter the expression of surface-exposed proteins through the processes of phase and antigenic variation. This potential for wide variability in surface-exposed structures allows the organisms to always have subpopulations of divergent antigenic types to avoid immune survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
113
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 206 publications
(181 reference statements)
0
113
0
Order By: Relevance
“…1B). In all of our strains (Table S1) recA expression is repressed to inhibit gene conversion in the pilin locus (35). Using uncoated beads that were treated like DNA-coated beads but without adding DNA, only 7% of the attempts resulted in binding, indicating that binding was mostly specific to DNA.…”
mentioning
confidence: 96%
“…1B). In all of our strains (Table S1) recA expression is repressed to inhibit gene conversion in the pilin locus (35). Using uncoated beads that were treated like DNA-coated beads but without adding DNA, only 7% of the attempts resulted in binding, indicating that binding was mostly specific to DNA.…”
mentioning
confidence: 96%
“…However, we found that dprA mutants exhibited increased RecA-dependent pilin variation compared to isogenic parental strains (Figs 3 and 4) suggesting a possible role of DprA in modulating this process. RecA-dependent pilin variation at the pilE locus in Neisseria has been the focus of intense research for decades [reviewed in Cahoon & Seifert (2011) and Rotman & Seifert (2014)] and current models invoke numerous recombination proteins (RecA, RecX, RecO, RecR, RecJ, RecQ, RecG, RuvABC) and the formation of quadraduplex DNA to initiate the non-reciprocal recombination process. Several components of the mismatch correction system have been shown to modulate pilin antigenic variation although the precise mechanism remains unknown (Criss et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Models of pilin variation invoke a double-strand break at the pilE locus resulting in a single strand invading the pilS locus (Rotman & Seifert, 2014). Therefore, it is possible that DprA binds this small singlestrand fragment during strand invasion and inhibits the formation of heteroduplex thereby reducing gene conversion and pilin variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations